Application of a dielectric barrier discharge plasma for heating plastic materials. (3rd May 2019) - Borin, Daniele; Sbaizero, Orfeo; Scuor, Nicola
Abstract: Dielectric barrier discharge (DBD) plasma is usually referred in literature as a form of cold plasma. Many applications of DBD plasma rely on this characteristic, which allow to treat also sensitive materials, including biological tissues, to exploit a range of different effects. Atmospheric pressure plasma treatment is regularly used on polymers to enhance surface properties such as wettability and adhesion. However, in the present work, we show that DBD plasma can also be used as an alternative for heating polymeric based materials, as an initial step for further industrial processing such as thermo-forming. In particular, the efficiency of the heating process has been measured, and a novel heating mechanism has been proposed based on the experimental results.